2020
DOI: 10.1080/26895293.2020.1757517
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 Improves the immune tolerance of human amniotic mesenchymal stem cells

Abstract: Tumor necrosis factor-α induced protein 8 like 2 (TIPE2) is one of the newly discovered negative regulators for body's immune balance. The present study aimed to investigate the effect of TIPE2 gene-modified human amniotic mesenchymal stem cells (hAD-MSCs) on immune tolerance. In this study, the TIPE2 over-expressed and the non-transfected hAD-MSCs were severally co-cultured with injured cardiomyocytes. Cell cycle and apoptosis were detected by flow cytometry. Cell viability was measured by MTT, and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, the mechanisms still require further investigations. The previous study of this project at the cellular level revealed that the overexpression of TIPE2 in hAD-MSCs significantly enhanced the ability of the cells in terms of both immune tolerance and anti-inflammation (19). Further exploration at the animal level was conducted in this study which aimed to identify the therapeutic effect It has been reported that TIPE2 mediates the signal transduction of both T cell receptors (TCRs) and toll-like receptors (TLRs), achieving negative regulation of inherent and adaptive immune responses, thereby maintaining immune homeostasis (22).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the mechanisms still require further investigations. The previous study of this project at the cellular level revealed that the overexpression of TIPE2 in hAD-MSCs significantly enhanced the ability of the cells in terms of both immune tolerance and anti-inflammation (19). Further exploration at the animal level was conducted in this study which aimed to identify the therapeutic effect It has been reported that TIPE2 mediates the signal transduction of both T cell receptors (TCRs) and toll-like receptors (TLRs), achieving negative regulation of inherent and adaptive immune responses, thereby maintaining immune homeostasis (22).…”
Section: Discussionmentioning
confidence: 83%
“…TIPE2 plays an important negative regulatory role in the intrinsic and adaptive immune responses (17,18). Our previous study findings demonstrated that TIPE2overexpressed hAD-MSCs elevated cell viability and attenuated cell apoptosis after co-culture with myocardial cells (19). To further clarify the regulatory role of TIPE2 in allogeneic heart transplantation, this study performed heart transplantation in mice.…”
Section: Introductionmentioning
confidence: 96%
“…These findings suggest that TIPE2 may play a vital role in PAH, which needs to be confirmed in our further experiments. In addition, Wang et al 20 suggested that TIPE2 contributes to promoting the viability of human amniotic mesenchymal stem cells. Consistently, our study found that TIPE2 overexpression promoted ADSC proliferation and migration via activating TLR4-ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Importantly, TIPE2 was reported to promote the viability of human amniotic mesenchymal stem cells. 20 Nevertheless, it is unclear the role of TIPE2 in ADSC function and the effects of the TIPE2-transfected ADSCs on injured PASMCs and PAECs in PAH.…”
Section: Introductionmentioning
confidence: 99%